Interview: Advances in dermatology. (May 2013) - Griffiths, Christopher EM
Christopher EM Griffiths speaks to Alisa Crisp, Commissioning Editor : Christopher EM Griffiths gained a first class BSc degree in Anatomy and qualified in Medicine from St Thomas' Hospital Medical School, London University (London, UK). He trained in Dermatology at St Mary's Hospital (London, UK), and at the University of Michigan (USA), where he was also on the Faculty for 4 years. He was appointed as the Foundation Chair in Dermatology at the University of Manchester (UK) in 1994 and is an honorary consultant dermatologist at Salford Royal NHS Foundation Trust (Salford, UK). Professor Griffiths developed the 'hub-and-spoke' model of dermatology services for Greater Manchester and introduced a multidisciplinary clinic for severe psoriasis – the Manchester Psoriasis Service – awarded Hospital Doctor Dermatology Team of the Year in 2002. At the University of Manchester he has served in various roles as: Head of Medicine and Neuroscience, Head of the School of Translational Medicine, Research Dean and Director of the Manchester Academic Health Science Centre. Professor Griffiths' named lectureships include: Sydney Watson Smith (2006); Parkes Weber (2007); Von Zumbusch, Munich (2008) and Hellerstrom, Stockholm (2010). He is cofounder of the International Psoriasis Council and is its President-Elect. He received the psoriasis lifetime achievement award of the American Skin Association in 2009. The Times of London named him as one of the UK's Top 200 doctors in 2010 and in 2011 he was appointed as an NIHR Senior Investigator and elected to Fellowship of the Academy of Medical Sciences. Professor Griffiths has been President of the British Association of Dermatologists (2004–2005); European Dermatology Forum (2010–2011) and British Society for Investigative Dermatology (1997–2000). He serves on the editorial boards of eight scientific journals and is an Associate Editor of the Journal of Investigative Dermatology . He has published 451 PubMed cited articles in scientific journals and has an H-Index of 73. Professor Griffiths is coeditor of Rook's Textbook of Dermatology and his research interests cover all aspects of psoriasis.